The Utilization of Digital Collaboration Technologies for Enhancing Work Productivity - Didik Setiadi; Ribut Julianto; Ranto Siswanto (Department of Informatics, Faculty of Science and Technology, UIN Prof. K.H. Saifuddin Zuhri, Purbalingga, Indonesia, 2025)
The Student Creativity Program (PKM) entitled Utilization of Collaboration Technology for Work Productivity aims to improve public understanding and skills in utilizing digital technology, especially during the transition from the COVID-19 pandemic to a hybrid work system. This program was implemented in Wanasari Village, Cibitung, targeting students and entry-level workers who need digital competencies to support academic and professional activities. The implementation methods included preparation, training, mentoring, evaluation, and reporting stages. The training focused on the utilization of collaboration tools such as Google Workspace and the implementation of digital-based work management practices. Participants were trained through practical sessions and guidance to improve their ability to manage documents, communicate, share information, and collaborate effectively using digital platforms. The results showed increased understanding and skills in using collaboration technology, improved digital teamwork capabilities, and the development of more efficient and productive work patterns. Although challenges such as limited internet access and different levels of digital literacy were encountered, the program was successfully conducted and achieved its objectives. Overall, this program provides a positive contribution to enhancing digital readiness, supporting work productivity, and preparing the community for an increasingly digitalized work environment today.